Multiplex Partial Nephrectomy, Repeat Partial Nephrectomy, and Salvage Partial Nephrectomy Remain the Primary Treatment in Multifocal and Hereditary Kidney Cancer - Baiocco, Joseph A.; Metwalli, Adam R. (Frontiers in Oncology, 2017)
The standard of care treatment for solitary renal cell carcinoma (RCC) tumors 4 cm or less is partial nephrectomy (PNx).1 However, multifocal kidney cancer presents unique challenges for treating physicians. Historically, total nephrectomy and hemodialysis with possible renal transplant later was the primary therapeutic strategy for these patients. Later, as nephron sparing surgical approaches improved, PNx became the standard of care for patients presenting with multifocal and hereditary RCC. Surgeries to remove multiple renal tumors simultaneously produce different perioperative outcomes2 and increased risk of complications.3,4 Due to these differences in technique and outcomes, the term multiplex partial nephrectomy (MxPNx) has been coined to designate these differences. Here we discuss the role that MxPNx continues to play in multifocal RCC.